Interprofessional Collaboration Practices in Stunting Management during Covid-19 Pandemic: A Scoping Review: English - Sivana Gian Regita; Sulistyaningsih Sulistyaningsih (Women, Midwives and Midwifery, 2022)
ABSTRACT Background: Globally, it is found that around 149 million children under five are stunted. In Asia and Africa, the prevalence of stunting in children under the age of five is known to reach 55% and 39%, respectively. Meanwhile, the stunting rate in Indonesia is 27.7%. New scientific findings related to personal factors that include knowledge, attitudes, self-efficacy, collaboration, and communication were found to increase interprofessional collaboration handling for stunting. Purpose: To review the practice of interprofessional collaboration in handling stunting during the Covid-19 pandemic. Methods: The method used in the scoping review consists of five stages, including identification of Scoping Review questions, identification of relevant studies, study selection, mapping of data to be compiled, summarized, and reported on the results. PEOs are a tool that can be used to assist health workers in searching the literature. Use, relevant databases are used, namely PubMed, Google Scholar, Science Direct. Results: A total of 71 articles were found on a search in the database. After screening titles and abstract references, 4 articles were found that had grades A and B. Interprofessional collaboration was found to be able to work well together in 2020 where this year was the start of the Covid-19 pandemic. In this case, the handling of stunting by the collaboration of the role of health workers is very necessary. For this reason, health workers carry out good management to reduce the risk of stunting, one of which is by providing health education and social assistance. Conclusion: Collaboration was found to be successful in increasing the knowledge of health workers between professions. Given the differences between theory and perceptions about communication and collaboration, Interprofessional collaboration, in this case, is a collaboration between Doctors, Nurses, Midwives, and Nutritionists in dealing with stunting through counseling according to their respective roles.